1983
DOI: 10.1159/000173600
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Reperfusion for the Treatment of Acute Myocardial Infarction: Postischemic Ventricular Dysfunction

Abstract: There has been recent interest in treating acute myocardial infarction with coronary reperfusion by fibrinolytic therapy. Experimental studies have shown that myocardial infarct size can be reduced by coronary reperfusion. However, return of cardiac function, high energy phosphate metabolism, and cardiac ultrastructure may be delayed within tissue which is salvaged by coronary reperfusion. This postischemic ventricular dysfunction is transient and has been termed the ‘stunned myocardium’ phenomenon. Although r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…Reimer et al (5) have reported that reperfusion-induced myocardial hemorrhage, as noted on gross inspection and histologic examination, was always confined to and never extended outside areas of myocardial cell necrosis. We have observed (24,30) that dogs subjected to a 2-h coronary occlusion followed by prolonged reperfusion usually had visible hemorrhage within the infarct, that the hemorrhage was smaller than the zone of myocardial necrosis, and that a nonhemorrhagic rim of infarcted tissue surrounded the zone of hemorrhage. Similar observations have been made in patients in whom reperfusion was carried out by thrombolysis or coronary bypass surgery (31 (35).…”
Section: Reperfusion-induced Hemorrhagementioning
confidence: 99%
See 1 more Smart Citation
“…Reimer et al (5) have reported that reperfusion-induced myocardial hemorrhage, as noted on gross inspection and histologic examination, was always confined to and never extended outside areas of myocardial cell necrosis. We have observed (24,30) that dogs subjected to a 2-h coronary occlusion followed by prolonged reperfusion usually had visible hemorrhage within the infarct, that the hemorrhage was smaller than the zone of myocardial necrosis, and that a nonhemorrhagic rim of infarcted tissue surrounded the zone of hemorrhage. Similar observations have been made in patients in whom reperfusion was carried out by thrombolysis or coronary bypass surgery (31 (35).…”
Section: Reperfusion-induced Hemorrhagementioning
confidence: 99%
“…While this increase is dramatic in irreversibly injured cells, it may also be seen transiently and to a lesser extent in reversibly injured tissue (24,25). This so-called "explosive" cell swelling of irreversibly injured cells (26) appears to be caused by an ischemia-induced sarcolemmal abnormality which causes a serious defect in regulation of cell volume and which is associated with marked increases in tissue water, sodium, chloride, and calcium.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental animal studies have extensively demonstrated the relationships between the duration of ischemia and severity of myocardial ischemic lesions and the histologic and ultrastructural findings of "stunned myocardium". [2][3][4][5][6][7][8] However, little is known about the histopathologic substrates of "stunned myocardium" in humans, because the prognosis in patients with "stunned myocardium" and its sequelae appears to be good in the absence of superimposed ischemic lesions or other severe medical illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…or over in size were not found macroscopically in the transverse sections. In experimental studies, a majority of the hematoxylin-eosin-stained sections of "stunned myocardium" show normal or nearly normal light microscopic features, [2][3][4] or, rarely, two or three hypereosinophilic myocytes are noted mainly in the subendocardium. 4) In Case 1, however, histological sections showed scattered necrotic foci in the subendocardium and trabeculae of the jeopardized zone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation